Italy : Detailed Assessment of Compliance with the Committee for Payment and Settlement Systems (CPSS) Core Principles for Systemically Important Payment Systems. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper presents findings of the Detailed Assessment of Italy's Compliance with the Committee for Payment and Settlement Systems (CPSS) Core Principles for Systemically Important Payment Systems. At present, the Italian banking system is subject to significant challenges resulting from slowing economic growth, and low and declining interest rates, which have resulted in pressures on margins and a need to diversify sources of income. Banca d'Italia RTGS System for Large-Value Payments (BIREL) enables participants to make final and irrevocable transfers between the settlement accounts they hold with the Banca d'Italia.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet